Evolution of Drug Supply for Psoriasis from 2010 to 2022 – Real-World Claims Data Analysis in Germany - Hagenström K; Klinger T; Stephan B; Augustin M (Psoriasis: Targets and Therapy)
Kristina Hagenström, Theresa Klinger, Brigitte Stephan, Matthias Augustin Institute for Health Services Research in Dermatology and Nursing (IVDP), University Medical Center Hamburg-Eppendorf (UKE), Hamburg, GermanyCorrespondence: Kristina Hagenström, Institute for Health Services Research in Dermatology and Nursing (IVDP), University Medical Center Hamburg-Eppendorf (UKE), Martinistraße 52, Hamburg, 20246, Germany, Tel +49 40 741059513, Fax +49 40 74105534, Email k.hagenstroem@uke.dePurpose: The management of psoriasis has undergone substantial evolution; however, the long-term prescription trends remain ambiguous. This study utilised a comprehensive data set of psoriasis drug prescriptions in Germany from 2010 to 2022, with the objective of evaluating the evolution of treatment modalities over time.Methods: A retrospective longitudinal claims data analysis on systemic biologicals, non-biologicals, and topical treatments for psoriasis was conducted covering prescription rates, medical costs from the payer’s perspective, and defined daily doses (DDDs).Results: Psoriasis prevalence increased slightly from 2.6% in 2010 to 2.7% in 2022. During this period, the proportion of persons receiving prescriptions rose from 55.0% in 2010 to 57.4% in 2022. By 2022, 46.2% of these persons received topical treatments, 13.0% systemic glucocorticosteroids (SCS), 6.7% non-biologicals, and 6.2% biologicals. Compared to 2010, the use of biologicals increased by 449.8%, SCS by 12.6%, non-biologicals by 13.9%, while topical treatments decreased by 3.2%. The annual cost per person treated with a biologic decreased from € 16,315 to € 13,412, while non-biologic and topical therapy costs increased slightly. Adalimumab was the most frequently prescribed systemic drug, followed by ustekinumab and secukinumab. The highest mean costs per-person were for ustekinumab (€ 19,717) and risankizumab (€ 16,986).Conclusion: In more than a decade, the use of innovative systemic drugs, especially biologicals, in Germany has increased substantially. Despite their high cost, biologic expenses per person have slightly decreased over time.Keywords: statutory health insurance, claims data, treatment, prescription